"الجباية البيئية وفعاليتها في المؤسسة الاقتصادية دراسة حالة عينة من الأكاديميين والمهنيين لولاية الوادي " - عمار, دبار; محمد العربي, ميدة (University of eloued جامعة الوادي, 2020)
"يهدف البحث إلى دراسة فعالية الجبائية البيئية في للمؤسسات الاقتصادية وبيان إجراءاتها وأساليبها ومخاطر الناجمة عنها ولتحقيق هذا الهدف، قمنا بتقديم إطار نظري لموضوع الدراسة وثانيهما ميداني أو تطبيقي تمثل في إجراء دراسة ميدانية عن طريق استبيان، وهذا لمعرفة مدى تأثير مساهمة الجبائية البيئية في فعالية الحماية البيئية للمؤسسات الاقتصادية وذلك بالاعتماد على المنهج الوصفي التحليلي . وقد خلصت الدراسة إلى أن استخدام الجباية البيئية والمتمثلة في تطبيق مختلف الإجراءات والتشريعات والقوانين والضرائب والرسوم البيئية المطبقة حالية لها دورا فعالا في مكافحة التلوث والتدهور البيئي للمؤسسات الاقتصادية ، وهذا راجع إلى الكفاءة المهنية للمسؤولين بمدى تنميتهم بالوعي البيئي للحفاظ على البيئة. الكلمات المفتاحية: الجباية البيئية – الضرائب والرسوم البيئية- المؤسسات الاقتصادية . "" The research aims to study the effectiveness of environmental taxation in economic institutions and explain their procedures, methods and risks resulting from them. To achieve this goal, we have presented a theoretical framework for the subject of the study and the second field or application represented in conducting a field study through a questionnaire, and this is to know the extent of the impact of the environmental taxation in the effectiveness of environmental protection For economic institutions, based on the descriptive analytical approach. The study concluded that the use of environmental collection represented in the application of various procedures, legislations, laws, taxes and environmental fees currently applied have an effective role in combating pollution and environmental degradation of economic institutions, and this is due to the professional competence of officials to the extent of their development with environmental awareness to preserve the environment. Key words: environmental taxation - environmental taxes and fees - economic institutions. "
مذكرة ماستر اقتصاد وتسيير مؤسسات
Keywords: التكاليف البيئية, القياس المحاسبي لتكاليف البيئية, اإلفصاح المحاسبي لتكاليف البيئية, األداء البيئي.; environmental costs, environmental costs accounting, environmental cost accounting disclosure, environmental performance.